Genome-wide identification, characterization, and expression analysis of m6A readers-YTH domain-containing genes in alfalfa - Shugao Fan; Xiao Xu; Jianmin Chen; Yanling Yin; Ying Zhao (BMC Genomics, 2024)
Abstract Eukaryotic messenger RNAs (mRNAs) are often modified with methyl groups at the N6 position of adenosine (m6A), and these changes are interpreted by YTH domain-containing proteins to regulate the metabolism of m6A-modified mRNAs. Although alfalfa (Medicago sativa) is an established model organism for forage development, the understanding of YTH proteins in alfalfa is still limited. In the present investigation, 53 putative YTH genes, each encoding a YT521 domain-containing protein, were identified within the alfalfa genome. These genes were categorized into two subfamilies: YTHDF (49 members) and YTHDC (four members). Each subfamily demonstrates analogous motif distributions and domain architectures. Specifically, proteins encoded by MsYTHDF genes incorporate a single domain structure, while those corresponding to MsYTH5, 8, 12, 16 who are identified as members of the MsYTHDC subfamily, exhibit CCCH-type zinc finger repeats at their N-termini. It is also observed that the predicted aromatic cage pocket that binds the m6A residue of MsYTHDC consists of a sequence of two tryptophan residues and one tyrosine residue (WWY). Conversely, in MsYTHDF, the binding pocket comprises two highly conserved tryptophan residues and either one tryptophan residue (WWW) or tyrosine residue (WWY) in MsYTHDF. Through comparative analysis of qRT-PCR data, we observed distinct expression patterns in specific genes under abiotic stress, indicating their potential regulatory roles. Notably, five genes (MsYTH2, 14, 26, 27, 48) consistently exhibit upregulation, and two genes (MsYTH33, 35) are downregulated in response to both cold and salt stress. This suggests a common mechanism among these YTH proteins in response to various abiotic stressors in alfalfa. Further, integrating qRT-PCR with RNA-seq data revealed that MsYTH2, MsYTH14, and MsYTH16 are highly expressed in leaves at various development stages, underscoring their potential roles in regulating the growth of these plant parts. The obtained findings shed further light on the biological functions of MsYTH genes and may aid in the selection of suitable candidate genes for future genetic enhancement endeavors aimed at improving salt and cold tolerance in alfalfa.